Estado nutricional por antropometría y comportamiento alimentario en estudiantes de pregrado de la Universidad de Pamplona (@limentech, Ciencia y Tecnología Alimentaria, 2014)
This study identifies the nutritional status and some aspects of the eating behaviors of undergraduate students at the University of Pamplona. A survey was administered to a sample of 354 men and 445 women to characterize some eating behaviors and sociodemographic factors. Height, weight, and waist circumference were also measured. Data collection was conducted under the supervision and approval of the Ethics and Environmental Impact Committee of the University of Pamplona. Data analysis included frequency distributions of eating habits and calculation of means for anthropometric measurements. The average weight was 63 kg (SD: 12). The BMI in men was 23.48 kg/m2 and in women it was 22.97 kg/m2. Nutritionally, 69% of the university students were of normal weight, 20% were overweight, 6% were malnourished, and 5% were obese. Forty-one percent of students reported eating breakfast every day, 47% sometimes, and 11% skip breakfast. Thirty-six percent of students make a conscious effort to consume fruits and vegetables, while 64% do not. Intervention strategies are needed to promote healthy eating habits within the university setting.
Keywords: Anthropometry; Eating behavior; Nutritional status; University students; Malnutrition